Drug delivery of 6-bromoindirubin-3’-glycerol-oxime ether employing poly(d,l-lactide-co-glycolide)-based nanoencapsulation techniques with sustainable solvents - Czapka, Anna; Grune, Christian; Schaedel, Patrick; Bachmann, Vivien; Scheuer, Karl; Dirauf, Michael; Weber, Christine; Skaltsounis, Alexios-Leandros; Jandt, Klaus D.; Schubert, Ulrich S.; Fischer, Dagmar; Werz, Oliver (Journal of Nanobiotechnology, 2022)
Background: Insufficient solubility and stability of bioactive small molecules as well as poor biocompatibility may cause low bioavailability and are common obstacles in drug development. One example of such problematic molecules is 6-bromoindirubin-3'-glycerol-oxime ether (6BIGOE), a hydrophobic indirubin derivative. 6BIGOE potently modulates the release of inflammatory cytokines and lipid mediators from isolated human monocytes through inhibition of glycogen synthase kinase-3 in a favorable fashion. However, 6BIGOE suffers from poor solubility and short half-lives in biological aqueous environment and exerts cytotoxic effects in various mammalian cells. In order to overcome the poor water solubility, instability and cytotoxicity of 6BIGOE, we applied encapsulation into poly(d,l-lactide-co-glycolide) (PLGA)-based nanoparticles by employing formulation methods using the sustainable solvents Cyrene™ or 400 g/mol poly(ethylene glycol) as suitable technology for efficient drug delivery of 6BIGOE. Results: For all preparation techniques the physicochemical characterization of 6BIGOE-loaded nanoparticles revealed comparable crystallinity, sizes of about 230 nm with low polydispersity, negative zeta potentials around − 15 to − 25 mV, and biphasic release profiles over up to 24 h. Nanoparticles with improved cellular uptake and the ability to mask cytotoxic effects of 6BIGOE were obtained as shown in human monocytes over 48 h as well as in a shell-less hen’s egg model. Intriguingly, encapsulation into these nanoparticles fully retains the anti-inflammatory properties of 6BIGOE, that is, favorable modulation of the release of inflammation-relevant cytokines and lipid mediators from human monocytes. Conclusions: Our formulation method of PLGA-based nanoparticles by applying sustainable, non-toxic solvents is a feasible nanotechnology that circumvents the poor bioavailability and biocompatibility of the cargo 6BIGOE. This technology yields favorable drug delivery systems for efficient interference with inflammatory processes, with improved pharmacotherapeutic potential. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-01-14
Keywords: Drug delivery; Indirubin; Inflammation; Nanoparticles; PLGA; Sustainable solvents